Education On Mother's Anxiety And Husband's Support For The Election Of Akdr Family Planning In Dusun 1 Pekik Nyaring Central Bengkulu - Putri, Fika Aliyah; Anggraini, Tina; Kamila, Rahma; Sari, Liya Lugita; Rossita, Taufianie (Universitas Dehasen Bengkulu, 2024)
According to data from the World Health Organization (WHO), more than 100 million couples use contraceptives in the world using effective contraceptives, with 75% using hormonal contraceptives and 25% using non-hormonal contraceptives. Contraception in the world in 2019 reached 89%, while in 2020 there was an increase to 92.1%. In Africa, it is recorded that 82% of the population does not use contraception. In Southeast, South and West Asia, as many as 43% use contraception (WHO, 2021). Data from the World Health Organization (WHO) for 2020 shows that users of IUD contraceptives throughout the world are still below injectable contraceptives, pills, condoms and implants, especially in developing countries. Exposure to IUDs was below 10%, namely 7.3%, and other contraceptive devices was 11.7%. According to Pekik Nyering Community Health Center data, it was found that the number of IUD users was only 17 people, with a preliminary survey in hamlet 1 Pekik Nyaring numbering 0. Therefore, the author chose IUD/IUD KB counseling. Provide education to women of childbearing age (WUS) and provide knowledge about IUD/IUD contraception, explain the installation of the IUD contraceptive, how it works, types of IUD, mechanism, benefits, side effects, indications and installation time, provide questionnaires to mothers/ Suburban age women regarding the implementation of socialization carried out offline in the 1 Pekik Nyring hamlet hall, attended by 33 residents in 1 Pekik Nyard hamlet. This activity was attended by the cadres. The residents who were actively present in the IUD/AKDR intrauterine contraceptive education program activities. The socialization activities regarding Intrauterine Contraception Methods in the community in Dusun 1 Pekik Nyaring were proven to be effective in increasing knowledge, this was indicated by the results of the pretest and posttest which showed an increase in previous community knowledge. and after the socialization. This activity has an increasingly significant impact because the socialization participants are health cadres who are active in activities related to maternal and child health in the community and are active in inviting residents to pay more attention to health, especially family planning and women's reproductive health.